x=11+69/2 and x=11-69/2
2x + 6 + 9x = 39 11x + 6 = 39 11x = 39 - 6 11x = 33 x = 3
The equation -30 times -10 plus 11X equals -29. This is a math problem.
If 6x + 10 = 11x , then x=2.
X2 -11x +10=(x - 1 )(x - 10)
(11x - 1)(2x + 1)
x2 -11x-12= (x-12)(x+1)
The actual equation itself is the polynomial. There is no polynomial for it, and your question doesn't really make sense.
It is: (x+2)(x+9)
It is (x+2)(x+9) when factored
No. It factors to (11x - 13)(2x - 3)
It is an algebraic expression that can be simplified to: 11x+5
5x2+11x+2 = (5x+1)(x+2) when factored
Assuming the question is written as: x2+11x-12 This would factor to: (x+12)(x-1)